Intracranial suppurations surgically managed at Jos, North Central Nigeria: a nine-years retrospective review - Shilong, Danaan J.; Bot, Gyang M. (International Journal of Research in Medical Sciences, 2021)
Background: Intracranial suppurations are rare but can be fatal entities consisting of pus collection within the intracranial cavity. The aim of the study was to document the clinical and radiological findings in our patients and the outcome of treatment. Methods: A retrospective analysis of all consecutive patients presenting to the Jos University Teaching Hospital from January 2012 to December 2019. Data of interest were retrieved from their folders and entered into SPSS version 22 and descriptive statistics run on the variables. Results: There were 33 patients within this period, but only 21 had complete records and thus used for the analysis. The median age was 18 years (IQR=29), males accounted for 81% of the patients. The median time to presentation was 14 days (IQR=23). The most common cause of abscess in our series was trauma (surgical and non-surgical) in 38.1%, followed by contiguous spread from the ear or paranasal sinuses (23.8%). The most common symptom was fever occurring in 61.9%, followed by headache 42.8%. In two thirds of the patients, the abscess was intra-axial (the frontal lobe being the most common site). Patients were managed surgically with either a craniotomy (28.6%) or a burr whole (71.4%). A positive culture was obtained in 33.3% of cases. Conclusions: Intracranial suppurations are uncommon, but can occur in the setting of predisposing factors. A high index of suspicion is required to clinch the diagnosis.